KEPASTIAN HUKUM TERHADAP KEPEMILIKAN RUMAH KPR BAGI PEMBELI YANG BERITIKAD BAIK - Wakono, Nur; Rahmatiar, Yuniar; Abas, Muhamad (Collegium Studiosum Journal, 2023)
One of the issues that often arises in the implementation of home ownership loans (KPR) is the transfer of rights to the house carried out by the debtor to another party before the mortgage period ends without the knowledge of the bank and without the correct procedure. This phenomenon is known as transfer of rights or take over credit. This paper aims to evaluate the legal certainty for good faith buyers and the judge's consideration in decision No. 49/Pdt.G /2022/PN.Kwg. This research uses a Normative approach by analyzing legal materials. The results showed that the judge had decided that a good faith buyer could change the data of home ownership in accordance with legal certainty and the judge's consideration was correct in accordance with legal certainty where the plaintiff was a good faith buyer who could change the data of home ownership.